Dietary supplementation with a complex of cinnamaldehyde, carvacrol, and thymol negatively affects the intestinal function in LPS-challenged piglets - Zhang, Yanyan; Li, Qian; Wang, Zhongxing; Dong, Yi; Yi, Dan; Wu, Tao; Wang, Lei; Zhao, Di; Hou, Yongqing (Frontiers in Veterinary Science, 2023)
The effects of cinnamaldehyde, carvacrol and thymol complex (CCT) on the growth performance and intestinal function of piglets challenged with lipopolysaccharide (LPS) were determined. Colistin sulphate (CS) was as a positive control. Piglets (n=24, 32 days of age) were allocated to four treatments: Control group (fed basal diet), LPS group (fed basal diet), CS+LPS group (fed basal diet+50mg/kg CS), and CCT+LPS group (fed basal diet+50mg/kg CCT). Results showed that diarrhea rates of piglets were significantly reduced by CCT and CS supplementation respectively. Further research showed that CS supplementation tended to improve the intestinal absorption function in LPS-challenged piglets. Moreover, CS supplementation significantly reduced the contents of cortisol in blood and malondialdehyde in the duodenum and the activities of inducible nitric oxide synthase in the duodenum and ileum and total nitric oxide synthase in the ileum in LPS-challenged piglets. CS supplementation significantly increased the activities of sucrase in the ileum and myeloperoxidase in the jejunum in LPS-challenged piglets. CS supplementation significantly alleviated the reduced mRNA levels of immune-related genes (IL-4, IL-6, IL-8, IL-10) in mesenteric lymph nodes and jejunum and mucosal growth-related genes (IGF-1, mTOR, ALP) in LPS-challenged piglets. These results suggested that CS supplementation improved the intestinal function in LPS-challenged piglets by improving intestinal oxidative stress, immune stress, and absorption and repair function. However, although CCT supplementation improved oxidative stress by reducing (p<0.05) the content of malondialdehyde and the activity of nitric oxide synthase in the duodenum, CCT supplementation tended to aggravate the intestinal absorption dysfunction in LPS-challenged piglets. Furthermore, compared with the control and LPS groups, CCT supplementation remarkably elevated the content of prostaglandin in plasma and the mRNA levels of pro-inflammatory factor IL-6 in mesenteric lymph nodes and jejunum, and reduced the activity of maltase in the ileum in LPS-challenged piglets. These results suggested that CCT supplementation had a negative effect on intestinal function by altering intestinal immune stress response and reducing disaccharidase activity in LPS-challenged piglets. Compared to CS, CCT supplementation exhibited a negative effect on intestinal function, suggesting whether CCT can be as an effective feed additive still needs further study.